Alcune riflessioni sulla conservazione e valorizzazione degli antichi edifici ludici e teatrali gallo-romani - Emanuele Romeo (Restauro Archeologico, 2015)
The french archaeological heritage of the classical age has been subject to phenomena that have caused either its abandonment or the continuation of its use, its transformation or the loss of its integrity. In particular, theatres, amphitheatres and circuses are often now in ruins after experiencing seasons of transformation, conversion to new uses and restoration: processes that have ensured the survival of these buildings through a continuous integration in urban activities. Based on these premises, the paper presents the results of a research aimed to the preservation of this heritage, suggesting strategies for its valorization that, in accordance with the requirements of the contemporary world, propose a project for fruition that must be compatible with such goods.